Dietary lotus seed powder enhances semen quality and storage stability in Mia roosters - PHAN NHAN; NGUYEN MINH TRI (Asian Journal of Agriculture, 2025)
Abstract. Nhan P, Tri NM. 2025. Dietary lotus seed powder enhances semen quality and storage stability in Mia roosters. Asian J Agric 9: 598-606. Semen quality, a key determinant of reproductive efficiency in poultry, plays a crucial role in breeding programs and in the conservation of indigenous genetic resources. Natural dietary supplements with antioxidant activity may improve sperm function and preservation. Lotus seed powder (Nelumbinis semen) is rich in bioactive compounds with antioxidant and membrane-stabilizing properties, but its effects on avian reproduction remain unexplored. This study represents the first report in avian species evaluating the impact of dietary lotus seed powder supplementation on semen quality and storage stability in Mia roosters, a Vietnamese indigenous breed. Thirty healthy roosters (10-11 months) were fed either a control diet or diets supplemented with 2% or 4% lotus seed powder for 60 days. Semen was collected every three days and assessed for volume, concentration, motility parameters, morphology, viability, membrane integrity, and chilled storage stability (0-24 h at 4°C). Compared with the control (C), T2 showed higher semen volume (0.48±0.05 mL vs 0.42±0.05 mL), sperm concentration (3.47±0.27×109/mL vs 3.21±0.26×109/mL), VSL (46.25±3.15 µm/s vs 42.35±3.12 µm/s), and viability (91.03±2.68% vs 87.46±2.85%). Abnormal morphology decreased from 9.84±1.21% in C to 8.15±1.12% in T2. Motility after 24 h storage remained higher in T2 (63.20±4.15%) compared with C (51.81±4.91%). Dietary lotus seed powder, particularly at 4% inclusion, significantly improves semen quality by enhancing sperm motility, viability, and membrane integrity, while also prolonging chilled storage stability in Mia roosters. These outcomes underscore its potential as a natural reproductive enhancer with applications in Artificial Insemination (AI) and the conservation of indigenous poultry genetic resources.